EXAMINING THE INFLUENCES OF CITIZEN FACTORS ON THE COCREATION BEHAVIORS OF ONLINE PUBLIC SERVICES IN A SMART CITY - Kusumastuti, Ratih Dyah; Nurmala, Nurmala; Rouli, Juliana (Journal of Environmental Science and Sustainable Development, 2026)
As smart cities increasingly rely on digital platforms to deliver public services, citizen participation becomes essential for ensuring effective and sustainable service delivery. However, limited research has examined which citizen-related factors drive co-creation behaviors in smart city contexts, particularly in emerging economies. This study aims to investigate the factors that influence the co-creation behaviors of online public services in five smart cities in Indonesia through the city’s digital platform and online social network (OSN). This study analyzes whether citizen factors, namely, perceived benefits over the city and OSN friends, trust in the city and OSN friends, and self-efficacy, affect co-creation behaviors leading to citizen satisfaction. A survey with 1009 respondents was conducted in Jakarta, Bandung, Semarang, Surabaya, and Denpasar, and the collected data were analyzed using covariancebased structural equation modelling. The results show that perceived benefit from OSN friends is the dominant factor that affects co-creation behaviors, which in turn affects citizen satisfaction. These findings highlight the critical role of OSN in fostering co-creation and suggest that integrating online public services with OSN can enhance service quality and citizen satisfaction.